Aging-related structural change in 3D extracellular matrix affects its mechanics. (August 2022) - Park, Seungman; Kim, Byunggik
Highlights: Aging induces marked alterations in the structural properties of the ECM. We develop a computational model to predict aging-related changes in the ECM. ECM fiber orientation is leveraged as an aging-related key parameter. We design and construct different fibrous structures to mimic aging and young ECM. Abstract: Aging induces marked alterations in the structural, mechanical, and transport properties in the extracellular matrix (ECM). To provide computational data on the impact of aging-related changes on ECM mechanical quantities and transport properties, we developed a computational model for the aging-related ECM fibrous network. A finite volume method was utilized to calculate the velocity field, pressure loss, hydraulic conductivity and drag force. Our results quantitatively demonstrated that the hydraulic conductivity in most of the aging ECM-mimetic fibrous networks tends to be significantly lower than young ECM-mimetic fibrous networks, while pressure loss and drag force show the opposite trend. All these findings highlight that such altered mechanical quantities and transport properties during aging can be important biological cues to assess the aging process and eventually provide insights in treating aging-related diseases.